Strategy, Structure, and System: Literature Study of Basic Management Implementation in the Public Sector - Asak, Ni Ketut Mahayanti Pramiswari (The Journal of Financial, Accounting, and Economics, 2024)
Public sector management plays a key role in improving the efficiency and effectiveness of public services. This study aims to evaluate the application of managerial principles in the public sector, highlighting the importance of integrated strategy, structure, and system management. Factors such as human resource capacity, use of information technology, and the application of transparency and accountability principles were found to have a significant impact on public sector performance. The study also identified key challenges in implementing managerial strategies, including resource constraints and bureaucratic barriers. As part of this research, a systematic approach in analyzing relevant literature through the Systematic Literature Review (SLR) methodology was used to provide in-depth insights into public sector management. The research findings suggest that flexible and decentralized organizational structures can accelerate decision-making and improve responsiveness to community needs. Management information systems (MIS) are important tools in improving efficiency and transparency. The results of this study provide practical guidance for policy makers in designing more effective systems and structures in the public sector.